Adipose Tissue, Inflammation (Meta-inflammation) and Obesity Management - Anna Meiliana; Nurrani Mustika Dewi; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2015)
BACKGROUND: Obesity-induced inflammation contributes to the development of type 2 diabetes, metabolic syndrome, and cardiovascular disease.CONTENT:The last decade has seen a sharp increase in our appreciation for the macrophage as a critical regulator of metabolic status in obesity. Activation of adipose tissue (AT) macrophages within fat depots is coupled with the development of obesity-induced proinflammatory state and insulin resistance (IR). The activation of classically activated M1 macrophages at the expense of anti-inflammatory M2 macrophages has been causally linked to the development of AT inflammation and metabolic syndrome, a pathophysiological state aptly termed as ‘metainflammation’. It is recognized that several proinflammatory cytokines, including interleukin (IL)-1β, are implicated in disrupting insulin signaling. Our developing appreciation of links among obesity, inflammation and cardiovascular disease will require multiple complementary approaches to leverage new concepts into translatable outcomes. Careful characterization of human patients, particularly analysis of AT distribution, will be needed to stratify subjects that are most likely obese/metabolically healthy from those that are obese/metabolically unhealthy.SUMMARY: It has been suggested that individuals with the condition known as metabolically healthy obese (MHO) may not have the same increased risk for the development of metabolic abnormalities as their non-metabolically healthy counterparts. A complications-centric model for the medical management of obesity emphasizes the identification and staging of complications, and treatment paradigm directed at patients who would gain the most benefit from weight loss.KEYWORDS: obesity, inflammation, insulin resistance, M1/M2 macrophage.